Determination of the Influence of Chronic Periodontitis on Pulp Sensibility by Means of Electric and Thermal Cold Testing - Neves, Vanessa C.Q.; Toledo, Benedicto E.C. [UNESP]; Camargo, Gabriela A.C.G.; Souza, Alessandra A.; Zuza, Elizangela P. (Elsevier, 2017)
Introduction Communication between pulp and periodontal tissue has been well established. However, it is unknown when periodontal disease begins to affect the clinical response of pulp tissue. The aim of this study was to assess the influence of periodontal severity on pulp sensibility by means of electric and thermal cold testing. Methods The teeth assessed in this study were allocated into 3 groups considering radiographic alveolar bone loss (ABL) as follows: slight periodontitis (SP, ABL ≤7 mm without reaching the apex, n = 25), moderate periodontitis (ABL >7 mm without reaching the apex, n = 23), and severe periodontitis (SvP, ABL >7 reaching the apex, n = 8). Gingival recession (GR), probing depth (PD), and clinical attachment level (CAL) were also measured. Results The results showed higher levels of PD and CAL in the SvP group compared with the SP group (P <.05), with no significant difference in GR (P >.05). The SvP group showed significant ABL compared with the other groups (P >.05). The SP group showed a significant number of teeth with a positive pulp response, whereas the SvP group showed a significant number of teeth with a negative pulp response (P <.05); no significant differences were observed between the thermal cold and electric tests (P >.05). Conclusions Within the limits of this study, it can be concluded that pulp clinical involvement with a negative response to thermal cold and electric testing occurs only in the most advanced stage of chronic periodontitis with apical involvement.
Keywords: Chronic periodontitis; dental pulp; endodontics